Identification of genotypes of Influenza A virus in Malaysia - Rahman, MM; Wong, KK; Isahak, I; Rashid, ZZ; Alfizah, H (Professional Medical Publications, 2024)
Objective: Influenza is considered as an emerging disease until today. The present study was undertaken to determine the prevalent genotypes of Influenza A virus in Malaysia. Methods: Influenza A virus was identified from respiratory specimens by real-time reverse transcriptase polymerase chain reaction (rRT-PCR). Phylogenetic analysis of the identified isolates was performed and genotypes were detected. Results: A total number of 505 throat swabs and nasopharyngeal aspirates were examined by rRT-PCR at Universiti Kebangsaan Malaysia Medical Centre (UKMMC) in which 65(12.87%) were positive for influenza A. The identified isolates were successfully genotyped by phylogenetic analysis. The identified influenza A genotypes were: H1N1 (42), H3N2 (20) and H5N1 (3). Conclusion: The findings indicated that 3 genotypes were circulating in Malaysia during 2011 in which H1N1 was the predominant. Results added new genotype (H5N1) identification record in Malaysia that may be added in data base of WHO and CDC.